The Power of Hotel Clustering for Enhanced Market Competitiveness - Izzatovna, Abdullaeva Zulfiya (International Journal on Orange Technologies, 2023)
In today's highly competitive hotel industry, the clustering methodology has emerged as an effective form of management for enhancing market competitiveness. This article presents a comprehensive overview of clustering as a strategy for the hotel business, highlighting the work of various researchers in this field. Drawing on the success of the Samarkand region in Uzbekistan, this article underscores the potential of clustering to improve the quality of service in hotels and contribute to the socio-economic development of the region. By exploring the role of tourism clustering in the hotel business, this article concludes that clustering can attract a larger flow of tourists and investments, thereby boosting the overall growth and success of the hotel industry.